2019
DOI: 10.1192/bjp.2019.161
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year employment patterns of patients with first-episode schizophrenia-spectrum disorders: comparison of early intervention and standard care services

Abstract: BackgroundLittle is known about long-term employment outcomes for patients with first-episode schizophrenia-spectrum (FES) disorders who received early intervention services.AimsWe compared the 10-year employment trajectory of patients with FES who received early intervention services with those who received standard care. Factors differentiating the employment trajectories were explored.MethodPatients with FES (N = 145) who received early intervention services in Hong Kong between 1 July 2001 and 30 June 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…A previous study of general patients with schizophrenia also reported that being male is an independent positive predictor of employment 16. On the other hand, a recent study of patients with first-episode schizophrenia-spectrum disorders reported that females who receive standard care services have better employment outcomes than men 18. There was no sex difference in employment in the present study.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…A previous study of general patients with schizophrenia also reported that being male is an independent positive predictor of employment 16. On the other hand, a recent study of patients with first-episode schizophrenia-spectrum disorders reported that females who receive standard care services have better employment outcomes than men 18. There was no sex difference in employment in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…The employment rate among patients with schizophrenia is also lower than that of the general population,1,5,912 ranging from 4% to 50.4%,13 with most studies reporting a rate between 10–20% 11,14. The severity of negative symptoms,15,16 cognitive dysfunction,17 early onset age and duration of illness,15 higher rate of early relapse,18 older age,16,17 and lower education,16 have all been reported to be negatively associated with employment outcomes 13,19. Work history is positively associated with employment rate 14.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that 71% of the patients with schizophrenia living in the community were unemployed [63]. The number of relapses during the first three years and low level of education are predictors for unemployment among patients suffering from first-episode schizophrenia-spectrum disorders [64]. Apart from public stigma, patients often have self-stigma which lowers their self-esteem.…”
Section: Stigma Related To Psychiatric Illnesses and Advancement Of Amentioning
confidence: 99%
“…Relapses have a significant impact on the outcomes of patients. Studies have shown that early relapses are associated with increasing suicide mortality (Chan et al, 2018) and poor long-term trajectories of employment (Chan et al, 2020). About one in six patients was found to exhibit protracted impairment after relapse (Emsley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%